Peningkatan Literasi Kesehatan Mental Ibu Berbasis Masyarakat pada Tenaga Kesehatan dan Kader di Kabupaten Banyuwangi: Increasing Community Based Maternal Mental Health Literacy among Health Workers and Cadres in Banyuwangi District - Sulistyorini, Yuly; Prayoga, Diansanto; Ariana, Atika Dian; Damayanti, Nyoman Anita; Anis, Wahyul; Lailiyah, Syifa’ul; Rosyida, Aulia; Utami, Indah Tri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Mental health problems in pregnant women are one of the health problems that have not been handled optimally in Banyuwangi Regency both during pregnancy and postpartum. Mental health screening of pregnant/postpartum women in antenatal care services is currently not running optimally because not all health workers have the ability to screen. Likewise, cadres as the spearheads in the community who assist pregnant/postpartum women in their area. Therefore, increasing literacy both knowledge and practice of mental health screening is needed. This capacity-building training activity aims to increase knowledge and skills in mental health screening using SRQ-20 to health workers and cadres. The 88 training participants consisted of 48 health workers and 40 cadres representing all sub-districts in Banyuwangi District. The results of this activity show that there are differences in knowledge and skills before and after with a value of p = 0.000 (health workers) and p = 0.000 (cadres). The average score before training also increased from 65.972 to 90.972 (health workers) and 41.833 to 71.667 (cadres) with a maximum score of 100. This activity is expected to improve antenatal care services and the participation of health workers and cadres in conducting mental health screening at puskesmas and their assisted areas.